2012
DOI: 10.1016/j.engstruct.2012.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of frictional contact effects in push-out tests

Abstract: This paper proposes an accurate and efficient 2D nonlinear finite element model to investigate the mechanical behaviour of the shear connection between prefabricated concrete slab and steel girder in composite bridges. Beside material nonlinear constitutive laws and 4-noded plane elements, frictional contact finite elements are introduced in the model at the steelconcrete interface between the girder flange and the concrete slab, between the studs and the embedding concrete and at the base of the concrete slab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 13 publications
(16 reference statements)
2
27
0
1
Order By: Relevance
“…One observes that the shear force F is mostly supported by the bottom stud-rows. Referring to [15], the behavior of this located zone subjected to a shear force is similar to the case of a standard push-out test. One distinguishes 3 parts of the shear force transmitted by the joint: -First part supported by the horizontal stud-rows.…”
Section: Longitudinal Stresses In Horizontal Stud-rowsmentioning
confidence: 82%
See 3 more Smart Citations
“…One observes that the shear force F is mostly supported by the bottom stud-rows. Referring to [15], the behavior of this located zone subjected to a shear force is similar to the case of a standard push-out test. One distinguishes 3 parts of the shear force transmitted by the joint: -First part supported by the horizontal stud-rows.…”
Section: Longitudinal Stresses In Horizontal Stud-rowsmentioning
confidence: 82%
“…In previous companion papers [15,16] different configurations of push-out tests have been modeled using the 2D proposed model. For each test, comparisons between obtained numerical results and corresponding experimental results have showed a quite negligible contribution of the out-of-plane effects (along the axis perpendicular to the web surface of the steel section of the push-out specimen) showing the ability of the 2D proposed model to simulate correctly the behavior of composite sub-structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shear connectors were modelled by horizontal and vertical springs along the steel-concrete interface, and non-linear load-slippage curves representing realistic deformation characteristics were readily incorporated. Recently, Guezouli and Lachal [26] developed a new two-dimensional model to study the effect of steel-concrete contact and friction on the behaviour of stud shear connectors in push-out tests. It has been observed that the previous two-dimensional models with plane stress elements are able to predict satisfactorily the behaviour of the shear connectors both in terms of strength and ductility without any difficulty.…”
Section: Finite Element Analysismentioning
confidence: 99%